ASUHAN KEPERAWATAN PADA KLIEN HIPERTENSI DENGAN GANGGUAN KEBUTUHAN RASA AMAN NYAMAN DAN ISTIRAHAT TIDUR - Giffara Rana Septiart (2023)
Background : Hypertension is a universal health problem with a major risk factor for cardiovascular disease. Hypertension is known as a silent killer, or a disease that can make a person's death happen silently. Death can occur due to hypertension or someone who suffers from other congenital diseases caused by hypertension. Purpose: This research was conducted to gain experience and a real picture in providing nursing care to hypertensive clients with impaired need for a sense of security, comfort and sleep rest which includes assessment, nursing diagnoses, nursing plans, nursing implementation and nursing evaluation. Method: This case study implements nursing in hypertensive clients with impaired needs for security, comfort and rest sleep. Data collection was carried out by means of interviews, observations and physical examinations as well as documentation studies. Results: The nursing problems found in this case were acute pain, sleep pattern disturbances, and ineffective health care. The plan used by the author for clients is adapted to nursing problems that are applied based on outcome criteria, signs and symptoms, and the client's condition at the time nursing care is given. After carrying out nursing actions for 3x24 hours of the final evaluation results, two of the three diagnoses that the author adopted have been resolved. Conclusion: It is hoped that further research can carry out nursing care for hypertensive clients with impaired needs for a sense of security, comfort and good and proper sleep rest so that it is achieved in accordance with the nursing problems found in clients.